Adjunctive biomarkers for improving diagnosis of tuberculosis and monitoring therapeutic effects. Issue 4 (April 2015) - Hur, Yun-Gyoung; Kang, Young Ae; Jang, Sun-Hee; Hong, Ji Young; Kim, Ahreum; Lee, Sang A; Kim, Youngmi; Cho, Sang-Nae
Summary: Objectives: To identify host biomarkers associated with latent tuberculosis infection (LTBI), active tuberculosis (TB), and nontuberculous mycobacteria (NTM) diseases to improve diagnosis and effective anti-TB treatment. Methods: Active TB and NTM patients at diagnosis, recent TB contacts, and normal healthy subjects were recruited. Tuberculin skin tests, QuantiFERON-TB Gold In-Tube tests, and multiplex bead arrays with 17 analytes were performed. TB patients were re-evaluated after 2 and 6 months of treatment. Results: Mycobacterium tuberculosis ( M. tb ) antigen-specific IFN-γ, IL-2, and CXCL10 responses were significantly higher in active TB and LTBI compared with controls ( P  < 0.01). Only serum VEGF levels varied between the active TB and LTBI groups (AUC = 0.7576, P  < 0.001). Active TB and NTM diseases were differentiated by serum IL-2, IL-9, IL-13, IL-17, TNF-α and sCD40L levels ( P  < 0.05). Increased sCD40L and decreased M. tb antigen-specific IFN-γ levels correlated with sputum clearance of M. tb after 2 months of treatment ( P  < 0.001). Conclusions: Serum IL-2, IL-9, IL-13, IL-17, TNF-α, sCD40L and VEGF-A levels may be adjunctive biomarkers for differential diagnosis of active TB, LTBI, and NTM disease. Assessment of serum sCD40L and M. tb antigen-specific IFN-γ, TNF-α, and IL-2 levels could help predict successful anti-TB treatment in conjunction with M. tb clearance. Highlights: Analytes from individuals with active TB, NTM, or LTBI, and controls were analysed. Serum VEGF-A has diagnostic value for distinguishing active TB from LTBI. Active TB and NTM diseases were differentiated by analyte concentrations in serum. Levels of sCD40L and IFN-γ correlated with M. tb sputum clearance after treatment. Measurement of multiple analytes may improve diagnosis of TB, LTBI and NTM disease.